2004
DOI: 10.1158/1078-0432.ccr-0095-03
|View full text |Cite
|
Sign up to set email alerts
|

gp100209–2M Peptide Immunization of Human Lymphocyte Antigen-A2+ Stage I-III Melanoma Patients Induces Significant Increase in Antigen-Specific Effector and Long-Term Memory CD8+ T Cells

Abstract: Thirty-five HLA-A2؉ patients with completely resected stage I-III melanoma were vaccinated multiple times over 6 months with a modified melanoma peptide, gp100 209

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Alternatively, the use of proteins or peptides in combination with adjuvants should be considered: a recent clinical study of repeated injections of peptide and adjuvant has demonstrated continued boosting of CTL responses, reaching levels as high as 8% of CD8 ϩ cells. 47,48 Many preclinical studies have confirmed the ability of recombinant DNA vaccines to prime both humoral and cellular immune responses specific for recombinant gene products in mice and primates. 49 Indeed, we confirmed that DNA.Mel3 primes responses specific for the melan-A 26 -35 , tyrosinase 369 -377 and NY-ESO-1 155-167 epitopes in HLA-A2 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the use of proteins or peptides in combination with adjuvants should be considered: a recent clinical study of repeated injections of peptide and adjuvant has demonstrated continued boosting of CTL responses, reaching levels as high as 8% of CD8 ϩ cells. 47,48 Many preclinical studies have confirmed the ability of recombinant DNA vaccines to prime both humoral and cellular immune responses specific for recombinant gene products in mice and primates. 49 Indeed, we confirmed that DNA.Mel3 primes responses specific for the melan-A 26 -35 , tyrosinase 369 -377 and NY-ESO-1 155-167 epitopes in HLA-A2 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, these types of vaccines require high amounts of antigens to be effective as they will also be internalized and/or presented by other cells than DCs. [11][12][13][14][15] Additionally, the efficacy of these vaccines is often limited in a therapeutic setting. To enhance cross-presentation of tumor antigens and to achieve a better priming of T cells, current vaccination strategies focus at the in vivo delivery of tumor-antigens as proteins or peptides specifically to DCs.…”
Section: Introductionmentioning
confidence: 99%
“…A modified epitope, gp209-2M (33), which enhances peptide stability ninefold while not altering pMHC structure (34), is significantly more immunogenic (35) and has been widely used in clinical studies (36,37). Therefore, to closely mimic the clinical situation, we used this modified epitope in all subsequent in vitro and in vivo experiments.…”
mentioning
confidence: 99%